HIV/AIDS: A Persistent Health Issue for Women and Children in Mid and Far Western Nepal - Awasthi, KR; Adefemi, K; Tamrakar, M (Kathmandu University Medical Journal, 2015)
This article reviews the effect of male migration on the spread of HIV infections in mid and far-western Nepal. It explains the link between male mobility and HIV in women and children. Materials were collected by a systematic search of the databases and the websites of national and international agencies. HIV infection amongst male migrants was found to be high. Their risk behaviors such as unprotected sex with multiple partners and sex workers increase the risk of HIV infection. Substance abuse, loneliness, separation from families, peer pressure, long working hours and poor living conditions are factors that promote unsafe sex. Literacy and awareness about HIV is a key measure to decrease the prevalence of the disease and reduce social stigma among people affected. HIV is a major public health issue especially in Nepal with migration playing a major role in its spread. Negligence to sexual health and lack of comprehensive knowledge on the disease among male migrants are the major obstacles that have exacerbated the disease. There is a need for further research on the existing HIV cases affecting women and children of these two regions to get a clear picture of the gravity of the disease. Kathmandu University Medical Journal Vol.13(1) 2015; 88-93